Perfil dos ingressantes na Universidade do Estado de Mato Grosso: implicações do SISU no processo de democratização do acesso - BORGES, Luiz Francisco (2017)
The National Policy of Democratization of Access to Higher Education, instituted by the Unified Selection System - SiSU, Brings with it, mechanisms with the purpose of democratizing the vacancies in the public superior courses in the Institutions of Higher Education. In this context in 2012 the State University of Mato Grosso - UNEMAT joined the SiSU. Thus in 2013 UNEMAT will have two main forms of selection (SiSU in the first semester and Vestibular in the second semester) of each year. Research carried out stated that UNEMAT already had an access process, which was considered democratized, when referring to admission. The question that we raise in this research is: with the adhesion to the SiSU, the ticket remains democratized? Thus, the objective of this research is to understand the adherence to SiSU in the University Campus of Cáceres and its relation with the process of democratization of HEI. It adopts as a type of research the quanti-qualitative approach. The methodological procedure took place in four stages: in the first one, we performed the production balance; In the second analysis of documents; In the third, analysis of the database, specifically of the ENEM microdata, crossing them with the database of the institution; In the fourth stage we analyzed the vestibular data. The research instruments were the socioeconomic questionnaires of the ENEM and the Vestibular. A total of 1,414 ENEM questionnaires were analyzed during the period from 2012 to 2014 and 1,445 Vestibular questionnaires from 2013 to 2015, totaling 2,859 questionnaires from the 13 undergraduate students (Agronomy, Biology, Accounting, Computer Science, Law, Education Physics, Nursing, Geography, History, Letters, Mathematics, Medicine and Pedagogy) offered by UNEMAT / Cáceres. For data analysis, we adopted the descriptive statistics procedure.The results showed that there were several changes in UNEMAT after the implementation of SiSU as a form of entry. Thus: in the structure of the vestibular test, implementation of food aid and housing, creation of mechanisms to fill idle vacancies, implementation of affirmative policy for students from public schools. In relation to the profile of the students, we present the following results: a change in the profile when comparing the "number of people living in the same household", the students entering the university entrance examination are students who, for the most part, reside with up to three people, by SiSU, The majority of the students are enrolled with more than three people, ie SiSU enrolls families with larger numbers of people. The variable "exerts paid activity" there was difference in the profile. By the vestibular more students entered that declared that they exercised activity remunerated, whereas by the SiSU more students entered that at the time of the inscription they affirmed that they did not exercise paid activity. We also verified that the SiSU allowed the insertion of families with lower purchasing power. These families, with incomes of up to two minimum wages. The Vestibular, in turn, had an increase in the percentage of new entrants with a family income of three to five minimum wages. The profile changed after joining the SiSU, as we found more low-class students enrolled in the higher courses offered at the University Campus of Cáceres. We conclude that after the implementation of the SiSU, the ticket continues to be democratized. It is necessary to analyze if these students stay in the course, if they finish in the minimum time of payment. From these questions, new research should emerge regarding the policies of permanence.